IMPLEMENTASI PERANGKAT OTOMASI PADA BROODER LISTRIK AYAM SENTUL DENGAN INFORMASI BERBASIS PUSH NOTIFICATIONS - Ardiansah, Irfan; Anugrah, Eka; Setiawan, Iwan; Zaida, Zaida (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2023)
Sentul is one of local chicken species in which developed in Ciamis, West Java. In order to develop optimally, Sentul Chicken requires appropriate temperature. In the starter period, Sentul Chicken needs a constant temperature between 32˚C – 35˚C, to keep that temperature’s requirement, a brooder is needed. Brooder is an artificial heating that has function to fulfill the temperature’s provision for the starter period of Sentul Chicken. The aim of this research are to design a control of brooder automatically to meet the needs of temperature and light for Sentul Chicken’s starter period, designing a monitoring system utilizing push notifications technology which can support the process of supervising the brooder performance in order to comply temperature’s condition and light for the starter period of Sentul Chicken, and able to provide enhancement of the Sentul chicken’s weight in starter period. This research is using engineering method. The outcome of this research has proved that the tool of brooder can work automatically to fulfill temperature’s requirement (approximately between 32˚C – 35˚C for starter period of Sentul Chicken. Monitoring system using push notifications can be established by pushbullet application that able to observe brooder execution in real time and running for whole 24 hours, and this automatic controller can offer positive impact for the escalation of Sentul Chicken’s weight.